Creating Sustainable Fashion Collection Made Of Handloom Textile For Australian Market - Janet Rine Teowarang; Michael Nathaniel Kurniawan; Carla Van Lunn (Corak, 2022)
It is undeniable that the fashion industry has a huge impact on the environment, society and economy. In the midst of the movement of the fashion industry towards a sustainable concept, the COVID-19 pandemic came and stopped the movement of the global and domestic fashion industry. This caused a huge financial loss, but also provided an opportunity for the fashion industry to reimagine a better future. This article is the result of a practice-based research, where fashion designer of Allegra Jane creates a sustainable fashion collection made of eco-friendly handloom weaving for the Australian market. Through this practice, the designer learns about the cultivation of eri silkworms that produce peace silk, the processes involved in the making of natural weaving and dyeing that can be used to reinforce the concept of sustainable design, and the design process for Australians who are more receptive to clothing with a sustainable concept. This practice is useful for enriching literature in this field and providing examples of how the Indonesian fashion industry can begin to rise from the COVID-19 negative impacts.